Growth of weaned Friesian bull calves on a herb sward or with concentrate supplementation during late summer and early autumn. Issue 1 (2nd January 2017) - Pettigrew, E. J.; Morris, S. T.; Back, P. J.; Kenyon, P. R.; Berry, J.; Donald, A. J.; Lane, A. L.; Hickson, R. E.
ABSTRACT: Growth rates of weaned bull calves in late summer/early autumn can be low in a ryegrass/white clover-based system. This experiment compared the liveweight gain of weaned bull calves ( n  = 18 per treatment per year, in 3 replicates of 6 bulls) grazed on a herb sward comprised of chicory, plantain, red clover and white clover with bulls grazed on either pasture supplemented with 1.8 kg DM/day of concentrate, or pasture without supplementation. The experiment was repeated over three years. Bulls grazed on the herb sward grew faster ( P  < .05) than bulls grazed on pasture with or without concentrate supplementation. Liveweight gain of bulls grazed on pasture was less than for bulls supplemented with concentrate in two of the three years ( P  < .05). A herb sward is a better quality alternative to late summer/early autumn pasture, and could be used to increase liveweight gain of bulls during this period.